2005
DOI: 10.1292/jvms.67.713
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI Mutation in a Holstein Cow with Repeat Breeding in Japan

Abstract: ABSTRACT. Factor XI deficiency is an autosomal recessive coagulopathy in Holstein cattle. Affected cows have a tendency to show repeat breeding. Forty repeat breeding Holstein Friesian cows were selected and tested for the Factor XI mutation. Genomic DNA was isolated from the blood of the cows (n=40). Exon 12 of the Factor XI gene of the cows was amplified by PCR. One repeat breeding cow was heterozygous to the Factor XI mutation as indicated by the presence of two DNA fragments of 320 bp and 244 bp. The inser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 8 publications
2
21
1
4
Order By: Relevance
“…Furthermore, one Holstein cow with repeat breeding has been found to have the F11 deficiency heterozygous genotype in Japan [3]. However, no dams showed repeat breeding or abnormal bleeding at parturition in the F11 deficiency dams in the present study, and the rate of carriers was very high in the Japanese Black cattle.…”
Section: Discussioncontrasting
confidence: 60%
“…Furthermore, one Holstein cow with repeat breeding has been found to have the F11 deficiency heterozygous genotype in Japan [3]. However, no dams showed repeat breeding or abnormal bleeding at parturition in the F11 deficiency dams in the present study, and the rate of carriers was very high in the Japanese Black cattle.…”
Section: Discussioncontrasting
confidence: 60%
“…Therefore, it is possible that some cattle with F11 deficiency are normal. Ghanem et al (2005) reported that one Holstein cow with repeat breeding was found to have the F11 deficiency heterozygous genotype in Japan. However, no repeat breeding or abnormal bleeding at parturition has been reported in the F11 deficiency dams.…”
Section: Discussionmentioning
confidence: 99%
“…Holştayn sığır ırkında görülen bir nokta mutasyon, kan pıhtılaşma faktörlerinden XI yetmezliğine (FXID) neden olarak, bu M,50 bpDNA Ladder;5,homozygous control (244 bp);6,heterozygous control (244 bp,320 bp);1,2,3,4,7 ve 8 homozygous normal subjects mutasyon yönünden heterozigot bireylerde dahi döl tutma problemlerine neden olarak repeat breeder sendromunun gelişmesine etkisi olduğu bildirilmiştir (Ghanem et al 2005). Ghanem et al (2005) tarafından yapılan çalışmada, döl tutma problemi olan hayvanlar arasında FXID prevalansının % 2.5 olduğunu bildirilmiştir.…”
Section: Materyal Ve Yöntemunclassified
“…Ghanem et al (2005) tarafından yapılan çalışmada, döl tutma problemi olan hayvanlar arasında FXID prevalansının % 2.5 olduğunu bildirilmiştir. Benzer şekilde Polonya'da farklı çiftliklerden toplanan ve 28'inde repeat breeder, 9'unda ise tekrarlayan mastitis gösteren bireylerinde bulunduğu rastgele 140 baş Holştayn inek seçilerek FXID yönünden incelenmiştir.…”
Section: Materyal Ve Yöntemunclassified
See 1 more Smart Citation